2020
DOI: 10.1371/journal.ppat.1009025
|View full text |Cite
|
Sign up to set email alerts
|

TLR-9 agonist and CD40-targeting vaccination induces HIV-1 envelope-specific B cells with a diversified immunoglobulin repertoire in humanized mice

Abstract: The development of HIV-1 vaccines is challenged by the lack of relevant models to accurately induce human B- and T-cell responses in lymphoid organs. In humanized mice reconstituted with human hematopoietic stem cells (hu-mice), human B cell-development and function are impaired and cells fail to efficiently transition from IgM B cells to IgG B cells. Here, we found that CD40-targeted vaccination combined with CpG-B adjuvant overcomes the usual defect of human B-cell switch and maturation in hu-mice. We furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 53 publications
3
21
0
1
Order By: Relevance
“…The results in the hu-mice model are consistent with those of our previous CD40-targeted in uenza and HIV vaccine studies 13,14,18,19 and demonstrate that αCD40.RBD is a potent prime or boost vaccine for eliciting RBD-speci c T-and B-cell responses similar in magnitude to previously reported protective responses 11 . In addition, we previously showed that nanomolar amounts of αCD40 vaccines can elicit in vitro recall responses in PBMCs collected from individuals primed by the natural viral infection 18,22 .…”
Section: The αCd40rbd Vaccine Recalls Speci C Immune Responses In Cosupporting
confidence: 89%
See 1 more Smart Citation
“…The results in the hu-mice model are consistent with those of our previous CD40-targeted in uenza and HIV vaccine studies 13,14,18,19 and demonstrate that αCD40.RBD is a potent prime or boost vaccine for eliciting RBD-speci c T-and B-cell responses similar in magnitude to previously reported protective responses 11 . In addition, we previously showed that nanomolar amounts of αCD40 vaccines can elicit in vitro recall responses in PBMCs collected from individuals primed by the natural viral infection 18,22 .…”
Section: The αCd40rbd Vaccine Recalls Speci C Immune Responses In Cosupporting
confidence: 89%
“…Direct delivery of the antigen, which can additionally activate cell receptors, may also evoke a danger signal, stimulating an immune response without the need of additional immune stimulants, such as adjuvants. Among the various DC receptors tested, including lectins and scavenger receptors, we reported the superiority of vaccines targeting diverse viral antigens to CD40 expressing antigen-presenting cells in evoking strong antigen-speci c T-and B-cell responses [12][13][14][15][16] . Drawing from this knowledge, we developed a vaccine that targets the receptor-binding domain (RBD) of the SARS-CoV-2 spike antigen to the CD40 receptor (αCD40.RBD).…”
Section: Read Full Licensementioning
confidence: 99%
“…The antigen we used in this study was not HIV envelop protein so that we were not able to evaluate the neutralization activity of antibody induced by our vaccination stratagem. In another recent study, we proved that TLR-9 agonist plus CD40-targeting HIV envelop vaccination induced HIV-1 envelop-specific IgG with a diversified immunoglobulin repertoire and circulating Env-specific IgG-switched memory human B cells that exhibit clear signs of antigen-driven antibody affinity maturation ( 41 ).…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, single-cell RNA-sequencing was used in this model to characterize human innate immune cells in lymphoid tissues ( 83 ). Interestingly, despite the lack of isotype-switched mature B cells, hu-NRGs can still be a useful tool for certain vaccine investigations ( 84 ).…”
Section: Hsc Engraftment Models (Current Generation): Nog Nsg Nrg mentioning
confidence: 99%